Failure analysis of monopoles under simulated severe wind - Novo, Ace D.; Hernandez, Jaime Y. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Transmission monopoles are widely used nowadays; however, because of its tall height and slenderness, it is highly vulnerable to increased wind loads. This study simulated and identified the different modes of failure the monopoles may undergo when subjected to windspeeds of 200kph and 351 kph. Both static and dynamic analyses of a free-standing monopole, and three monopoles connected by cables or transmission lines were performed. The study utilized Computational Fluid Dynamics (CFD) and Finite Element Modeling (FEM) for the design and simulation, and the structural plans were obtained from the National Grid Corporation of the Philippines (NGCP). Modes of failure identified were local buckling at the base of the monopole or at the section right above its splice connections, as well as extreme deflection of the structure's unsupported end. The resulting maximum deflection did not reach the failure criterion which is 5% of the total height of the monopole. In addition, using the Maximum Equivalent Stress Theory, the structure was identified to have a safety factor greater than 1 for both windspeeds, manifesting its adequacy; though, it became critical at 351 kph winds because a minimum safety factor of 1.12 was obtained. This study, however, did not take into account the terrain conditions, imperfections in the manufacture or installation of the monopole, as well as the vibratory effects of the transmission lines since it was modeled as tension-only springs. Moreover, a simplified constant mean velocity was used, instead of the unsteady wind velocity which is more realistic. Through this study, the response or behavior of the monopoles on high wind events, such as typhoons, was understood; and the location of the critical section of the structure was also determined.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Electric lines -- Poles and towers; Failure analysis (Engineering)